Kontestasi Politik Perempuan Dalam Diskursus Gender dan Ekonomi Politik - Assidiq, Fajar; Triguswinri, Krisnaldo (CV RIFAINSTITUT, 2021)
The impact of the implementation of Law Number 2 of 2011 concerning Political Parties Including Women's Representation of at least 30 percent (Affirmative Action) is considered to have an impact on the quantitative aspect, but on the qualitative aspect. This is because the implementation of this policy tends to be interpreted as administrative settlement by political parties participating in the election, until finally the fact emerges that the growth of political recruitment in the regions is increasing. The purpose of writing this research is to reveal the qualitative reality of the application of the 30 percent quota for women in electoral politics in the midst of the big wave of oligarchy in Indonesia. Therefore, it is difficult for female candidates who are not incumbent candidates, oligarchs or who represent oligarchs to be able to win political contests. In the end, their contestation is only limited to complement the sufferer. Therefore, to reach the wealth of data, this article uses a qualitative method which aims to describe social phenomena that are holistic in nature in a natural setting. The result of this study is that economic modality is the only determining factor in the contestation of women in electoral politics in Indonesia, in this case in Cilacap as one of the regional representations in Indonesia.